A251 VERY EARLY ONSET INFLAMMATORY BOWEL DISEASE IN CHILDREN: A SINGLE CENTER EXPERIENCE OVER 15 YEARS - Alahmari, A A (J Can Assoc Gastroenterol, 2020)
BACKGROUND: Very-early-onset inflammatory bowel disease (VEOIBD) refers to an IBD diagnosis established before the 6th year of life, including a subset of patients with disease onset before the age of 2 years, known as infantile-onset IBD (IO-IBD) (1). VEO-IBD accounts for 15% of pediatric IBD and infantile IBD in approximately 1% (2,3). VEOIBD is considered to be a unique entity, and compared to adults with IBD, VEO-IBD children are more likely to present with extensive and treatment-resistant disease (4). AIMS: To analyze the clinical characteristics and management of patients diagnosed with very early onset inflammatory bowel disease (VEO-IBD). METHODS: A retrospective analysis of children diagnosed with VEO-IBD (age <6 years) at the Montreal Children’s Hospital from 2003–2018 was performed. Clinical data for VEO-IBD patients was collected to identify the clinical, biochemical, endoscopic and histological features of these patients and their clinical course until 2018. RESULTS: A total of 28 VEO-IBD patients (71% male) were included in this study. The median age of disease onset was 52 months. A diagnosis of Crohn’s disease (CD) or CD-like intestinal manifestations accounted for 89% of the VEO-IBD cases. Most patients had Crohn’s colitis (36%) of whom 50% had evidence of granulomatous Crohn’s disease; 11 patients[NAD1] [AQAB2] (39%) had upper gastrointestinal involvement. Over their progress of the disease, 4 patients (14%) required surgical intervention, while 11 patients (39%) required biologic therapy for maintenance therapy. Genetic[NAD3] [AQAB4] results were available for 5 patients out of 28 (18%) and 3 of them were identified to have monogenic IBD. CONCLUSIONS: In our center, the majority of patients with VEO-IBD had typical Crohn’s disease presentation. Most of the VEO-IBD patients responded well to the standard IBD treatment. Genetic studies were not done regularly for all of our patients, however, among those who had this testing performed 3/5 had an identifiable cause, suggesting that these patients should be investigated for an underlying genetic abnormality. FUNDING AGENCIES: None